Exercise pulse frequency reviewed from sport activities - Hambali, Sumbara; Gunawan, Gugun; Paembonan, M Saleh; Meirizal, Yopi (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2023)
Pulse rate is one indicator that indicates that the heart and circulatory systems in the body are working. The pulse can be used to analyze the functional abilities of a person's body, which of course is influenced by the activity of the body itself. The purpose of this study intends to examine the differences in the frequency of exercise pulse in terms of the type of activity or exercise, and in this study the type of sports activity carried out is the type of aerobic and anaerobic exercise. This type of research is quantitative descriptive research with a survey method approach. The number of respondents involved in the research was 31 people, namely students of the physical education study program STKIP Pasundan class of 2021. The research instrument used an exercise pulse test measured for 60 seconds on the wrist, while for research data analysis techniques using discriptive statistics. The results showed that the average frequency of the initial pulse or resting pulse of 31 respondents showed an average value of 79.9 times per minute, then after doing anaerobic exercise activity was 151.58 and the average pulse rate after doing aerobic activity was 149.58. The conclusion is that there appears to be a slight difference in the average frequency of the training pulse in terms of the type of training activity. Anaerobic exercise activity has a greater increase in average value than aerobic activity. Key word:: Pulse, Exercise, Sport Activities.